In some other life - Brody, Jessica (New York : Farrar Straus Giroux, 2017)
Kennedy chose to pursue the boy of her dreams rather than attend an elite private school, but as their romance ends she gets a glimpse of the not-so-perfect life she might have had.
Keywords: Choice -- Fiction; Dating (Social customs) -- Fiction; High schools -- Fiction; Schools -- Fiction; Family life -- Fiction; Decision making -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Families -- Juvenile fiction; YOUNG ADULT FICTION / Social Themes / Self-Esteem & Self-Reliance.; YOUNG ADULT FICTION / Social Themes / Dating & Sex; YOUNG ADULT FICTION / General; Young adult fiction